Selection of Proteolytic Lactic Acid Bacteria and the Potential as α-Glucosidase Inhibitor Activity During Milk Fermentation - Miftakhussolikhah Miftakhussolikhah; Tyas Utami; Puspita Lisdiyanti; Endang Sutriwati Rahayu (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Diabetes mellitus (DM) is a degenerative condition increasing globally, including in Indonesia, with a corresponding rise in death rates. One of the therapy methods for DM is the use of α-glucosidase inhibitor (AGI), with peptides identified as potential AGI-based food ingredients. Therefore, this study aimed to develop fermented milk products enhanced with AGI peptides by screening and identifying lactic acid bacteria (LAB) strains with proteolytic capabilities. The experiment was conducted in three main stages: (1) screening 32 LAB isolates for their proteolytic activity, (2) determining the optimal fermentation time for AGI production using selected proteolytic LAB strains, and (3) molecular identification of the selected LAB strains through 16S rRNA gene sequencing. The results showed that two isolates, SR17B and L23, identified as Lactiplantibacillus plantarum-pentosus SR17B and Lactiplantibacillus plantarum-pentosus L23, had high proteolytic activity and were capable of producing fermented milk with significant AGI activity of 35.94% and 35.15%, respectively. AGI activity progressively intensified during fermentation, peaking at 12 hours in both strains, indicating that this period of time was ideal for fermentation in order to have the largest inhibitory effect. These results suggested that selected LAB strains, particularly L. plantarum-pentosus SR17B and L23, could serve as functional starter cultures for development of fermented dairy products with antidiabetic potential.